2001
DOI: 10.1063/1.1338530
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectra of the chains HC2nH (n=8–13) in the gas phase

Abstract: The intense Σu+1←X1Σg+ electronic transition of the chains HC2nH (n=8–13) has been recorded in the gas phase using resonant two color two photon ionization spectroscopy. The gas phase frequencies lie ∼1300 cm−1 to the blue of the values in a neon matrix. These polyynes appear to be linear in both the ground and the excited state and, as for the polyynes, spectral and theoretical evidence for large bond alternation in the ground state is found indicating localized π orbitals on the C≡C units. These species are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
85
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 31 publications
11
85
1
Order By: Relevance
“…The PBE functional completely fails to describe the BLA for long chains, while spin-restricted HF theory predicts a very large BLA. Our DFT-HSE06 BLAs are in agreement with the values previously obtained using the B3LYP functional 27,70 , and are close to the MP2 results wherever the latter are available 71 ; however none of these BLA curves tends to the DMC BLA of polyyne as the chain length increases. By contrast, the CCSD(T) BLAs 37 of oligoynes appear to tend to a limit only slightly less than the DMC result for polyyne.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The PBE functional completely fails to describe the BLA for long chains, while spin-restricted HF theory predicts a very large BLA. Our DFT-HSE06 BLAs are in agreement with the values previously obtained using the B3LYP functional 27,70 , and are close to the MP2 results wherever the latter are available 71 ; however none of these BLA curves tends to the DMC BLA of polyyne as the chain length increases. By contrast, the CCSD(T) BLAs 37 of oligoynes appear to tend to a limit only slightly less than the DMC result for polyyne.…”
Section: Resultssupporting
confidence: 89%
“…The ground-state BLAs at the centres of oligoynes have previously been calculated using a variety of theoretical methods 27,37,70,71 ; some of the results are compared with our DMC and DFT data in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…They indicated that the main Raman features associated with stretching modes of the linear chains in both samples (C 10 H 2 @SWCNT and C 12 H 2 @SWCNT) are strongly enhanced around 2.1 eV, while the optical absorption observed when these molecules are dispersed in isotropic medium [57] or in the gas phase [58] occurs above 4.5 eV. They concluded that dipole-forbidden (dark) transitions of the polyynes that become active as a result of a symmetry breaking when the molecules are encapsulated inside the SWCNT.…”
Section: Study Of Polyynes Encapsulated Into Single-walled Carbon Nanmentioning
confidence: 99%
“…Plasma jet expansions have been used as a powerful technique for high resolution spectroscopy of molecular transients [1][2][3][4][5]. In recent years rotationally resolved spectra have been recorded for a number of radical and ionic species, combining plasma expansion techniques and sensitive spectroscopic detection techniques, such as LIF [1], REMPI-TOF [2], REMPI-PES [3], photo-detachment [4] and vibrational predissociation [5] spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years rotationally resolved spectra have been recorded for a number of radical and ionic species, combining plasma expansion techniques and sensitive spectroscopic detection techniques, such as LIF [1], REMPI-TOF [2], REMPI-PES [3], photo-detachment [4] and vibrational predissociation [5] spectroscopy. In the case of direct absorption experiments planar plasma expansions, i.e., expansions through a long and narrow slit, have turned out to be particularly useful.…”
Section: Introductionmentioning
confidence: 99%